Aryl Hydrocarbon Receptor Establishes a Delicate Balance between the Level of the Trace Amine Tryptamine and Monoamine Oxidase Activity in the Brain and Periphery in Health and Conditions such as Neurodegenerative, Neurodevelopmental, and Psychiatric Disorders - Kot, Marta (Current Neuropharmacology, 2025)
The purpose of this review was to analyse the literature regarding the correlation between the level of tryptamine, aryl hydrocarbon receptor (AHR) signalling pathway activation, and monoamine oxidase (MAO)-A and MAO-B activity in health and conditions such as neurodegenerative, neurodevelopmental, and psychiatric disorders. Tryptamine is generated through the decarboxylation of tryptophan by aromatic amino acid decarboxylase (AADC) in the central nervous system (CNS), peripheral nervous system (PNS), endocrine system, and gut bacteria. Organ-specific metabolism of tryptamine, which is mediated by different MAO isoforms, causes this trace amine to have different pharmacokinetics between the brain and periphery. Reactive oxygen species (ROS) generated by MAO can influence miRNA-CYP enzyme regulatory network and affect mitochondrial function. Tryptamine regulates AHR function by acting as an endogenous ligand for AHR, initiating AHR activation and inhibiting the expression of the CYP1A1 and CYP1A2 genes. The dysregulation of AHR signalling, triggered by endogenous tryptamine binding, can disrupt the regulation of prolactin levels. Depending on the tryptamine concentration and context, tryptamine can be beneficial or harmful. By acting as an agonist of inhibitory serotonin receptors and trace-amine associated receptor 1 (TAAR1) and an antagonist of excitatory serotonin receptors, it can engage in diverse physiological interactions with serotonin. Increased tryptamine production is observed under hypoxic conditions and is associated with hypoxia-inducible factor 1α (HIF-1α) activation, leading to AHR activation. Dysregulation of the association between tryptamine levels, AHR signalling pathway activation, and MAO activity is observed in Alzheimer’s disease (AD), Parkinson’s disease (PD), autism spectrum disorder (ASD) and schizophrenia.
Keywords: neurodegenerative